Cannabidiol effects in stem cells: A systematic review. - Mesas, Cristina; Moreno, Javier; Doello, Kevin; Peña, Mercedes; López-Romero, Juan Manuel; Prados, José; Melguizo, Consolación (Wiley, 2024)
Stem cells play a critical role in human tissue regeneration and repair. In addi- tion, cancer stem cells (CSCs), subpopulations of cancer cells sharing similar characteristics as normal stem cells, are responsible for tumor metastasis and resistance to chemo- and radiotherapy and to tumor relapse. Interestingly, all stem cells have cannabinoid receptors, such as cannabidiol (CBD), that per- form biological functions. The aim of this systematic review was to analyze the effect of CBD on both somatic stem cells (SSCs) and CSCs. Of the 276 articles analyzed, 38 were selected according to the inclusion and exclusion criteria. A total of 27 studied the effect of CBD on SSCs, finding that 44% focused on CBD differentiation effect and 56% on its protective activity. On the other hand, 11 articles looked at the effect of CBD on CSCs, including glioblastoma (64%), lung cancer (27%), and breast cancer (only one article). Our results showed that CBD exerted a differentiating and protective effect on SCCs. In addition, this molecule demonstrated an antiproliferative effect on some CSCs, although most of the analyses were performed in vitro. Therefore, although in vivo stud- ies should be necessary to justify its clinical use, CBD and its receptors could be a specific target to act on both SSCs and CSCs.
Keywords: Células madre; Células cancerosas; Cannabinoides - Receptores; Stem cells; Cancer stem cells; CBD; In vitro; In vivo